Mitochondrial Complex I Inhibitor Class A Rotenone Induced Toxicity In Rats, Adrenal Gland And The Ameliorative Effect Of Ferulic Acid Via Regulation Of Apoptosis Signaling (Journal of Pharmaceutical Negative Results, 2023)
Introduction Adrenal gland is a crucial part of our body. It is part of the Hipothalamo-Pituitary-Adrenal axis and the sympatho-adrenomedullary system. So, by turn, it acts as an essential stress regulator. Rotenone is a widely used organic pesticide providing a trustworthy model of Parkinson disease and causes neurotoxicity and systemic damage. Ferulic acid is a natural polyphenol that is widely present in vegetables and fruits with powerful antioxidant, and antiapoptotic properties Materials and methods Rats (Twenty -four) were randomly allocated into the following four equal groups: Ferulic acid was given orally to the control and Sham groups (50 mg/kg/d), Rotenone group received a daily dose of 2.5 mg/kg/d dissolved in 1ml of sunflower oil i.p, group 4 Rotenone + Ferulic acid Group. After 8 weeks, Serum samples were taken and Paraffin sections of the adrenal glands were stained with Hematoxylin and eosin, Luxol fast blue, and Bax and BCL2 immune staining. Results Rotenone has glucocorticoid-like action and disruptive histopathological effect in form of congested sinusoids, hemorrhage, and vacuolations. It also increases the BAX/BCL2 ratio indicating stimulation of the apoptosis process. Ferulic acid was proved to have an ameliorative effect in enhancing Rotenone induced adrenal gland toxicity. Conclusions Rotenone caused noticeable deterioration of rat adrenal gland via enhancing apoptosis. Co-administration of ferulic acid alleviated its destructive effects via regulation of apoptosis signals.